Em busca de um lugar ao sol: a viagem de Goethe à Itália - Geraldo José Diogo Filho (Confins)
This article presents a review of the geographical content of Goethe´s book "Journey to Italy". It analyzes the way the author describes the physical, environmental and human elements of the Italian territory in his travel report, among them the geology, relief, botany, climate, land use, art and culture of that country. In his narrative, Goethe often opposes the characteristics and conditions found throughout his expedition with those existing in Germany. In the course of landscapes very different from those of his homeland, the celebrated poet finds, in the south of the Alps, environmental conditions much more favorable to the study of nature, in view of the lower latitudes, the less frigid thermal conditions and the more luxuriant vegetation of the Mediterranean Region, as we tried to emphasize in the title of this article. The event of the journey is analyzed in the context of Goethe's biography, and it is concluded that the period that he spent in Italy, between 1786 and 1788, determined his formation as a natural scientist, providing him with materials, ideas and inspiration for the further development of various researches around nature.